Caveolin-1 Controls Vesicular TLR2 Expression, p38 Signaling and T Cell Suppression in BCG Infected Murine Monocytic Myeloid-Derived Suppressor Cells - John, Vini; Kotze, Leigh A.; Ribechini, Eliana; Walzl, Gerhard; Du Plessis, Nelita; Lutz, Manfred B. (Frontiers in Immunology, 2019)
Monocytic myeloid-derived suppressor cells (M-MDSCs) and granulocytic MDSCs (G-MDSCs) have been found to be massively induced in TB patients as well in murine Mtb infection models. However, the interaction of mycobacteria with MDSCs and its role in TB infection is not well studied. Here, we investigated the role of Cav-1 for MDSCs infected with Mycobacterium bovis Bacille-Calmette-Guerín (BCG). MDSCs that were generated from murine bone marrow (MDSCs) of wild-type (WT) or Cav1-/- mice upregulated Cav-1, TLR4 and TLR2 expression after BCG infection on the cell surface. However, Cav-1 deficiency resulted in a selective defect of intracellular TLR2 levels predominantly in the M-MDSC subset. Further analysis indicated no difference in the phagocytosis of BCG by M-MDSCs from WT and Cav1-/- mice or caveosome formation, but a reduced capacity to up-regulate surface markers, to secrete various cytokines, to induce iNOS and NO production required for suppression of T cell proliferation, whereas Arg-1 was not affected. Among the signaling pathways affected by Cav-1 deficiency, we found lower phosphorylation of the p38 mitogen-activated protein kinase (MAPK). Together, our findings reveal major differences to macrophages and dendritic cells (DCs). They implicate that i) Cav-1 is dispensable for the internalization of BCG, ii) vesicular TLR2 signaling in M-MDSCs is a major signaling pathway induced by BCG, iii) vesicular TLR2 signals are controlled by Cav-1, iv) vesicular TLR2/Cav-1 signaling is required for T cell suppressor functions.